Sosialisasi Pemanfaatan Molding Lilin Aromaterapi Karakter sebagai Stimulator Kegiatan Berwirausaha Anak Berkebutuhan Khusus di SLB B-C Bina Karya Insani, Pondok Bambu, Jakarta Timur - Nelius Harefa; Medyawanti Pane; Jendri Mamangkey; Zefanya Sipahelut; Ivan Julius Rajagukguk; Santhya Anaomi Tamansa; Ripaldo Sihombing; Tesalonika Febriani Zebua (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The socialization activity of the use of character aromatherapy candle molding is intended as an effort to stimulate the entrepreneurial activities of ABK in the context of providing options for economically valuable products that can be marketed on digital platforms. The participants of the activity numbered 25 people consisting of 17 ABK students, 8 educators and education personnel, which was carried out at SLB B-C Bina Karya Insani, Pondok Bambu, East Jakarta. The form of activity is in the form of socialization of the essence of entrepreneurship and socialization of the use of character aromatherapy candle molding in the context of producing specific products that have economic value and are worthy of being marketed on digital platforms. In the socialization process, random interviews were conducted with participants regarding their responses to the essence of entrepreneurial activities and the contribution of character aromatherapy candle molding. Based on the interview data, 61.11% of ABK students think that entrepreneurial activities are very important activities for them to do. 77.78% of ABK students think that the product is very suitable to be used as one of the product options that can be marketed on digital platforms, while 100% of educators and education personnel think that character aromatherapy candles are very suitable to be used as one of the entrepreneurial products that can be marketed on digital platforms. In the context of optimizing the use of molding, structured and continuous socialization and training are needed so that the contribution of molding can be increased.